Public demand urgency for equitable infrastructure restoration planning. (October 2021) - Chen, Yudi; Ji, Wenying
Abstract: Following disasters, public demand urgency is an essential element for equitable infrastructure restoration planning.However, public demand urgency has yet been well explored due to the lack of a conceptual definition and a reliable modeling approach. To fill the research gaps, this study defines public demand urgency as the negative sentiment expressed by communities on infrastructure services and proposes a systematic approach to model public demand urgency, thereby achieving enhanced infrastructure restoration planning. The proposed approach is capable of (1) accurately predicting the sentiment polarity for each infrastructure-related social media post through including the sentiment laden in infrastructure conditions; (2) reliably modeling public demand urgency with associated social media information uncertainty via a Bayesian-based method; and (3) equitably allocating restoration resources through incorporating the modeled public demand urgency. To illustrate the feasibility and applicability, we studied the electricity infrastructure restoration following Hurricane Laura in the Louisiana State, US. Results demonstrate that the proposed approach is capable of reliably indicating public demand urgency. The research outcomes benefit utility companies and emergency managers for enhanced relief resource allocation, thereby promoting social equity in infrastructure restoration.